2021
DOI: 10.1007/s10661-021-09575-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative health risk assessment of nitrate in drinking groundwater resources of urban and rural regions (Isfahan, Iran), using GIS

Abstract: to NO 3 − exposure through consumption of drinking water was assessed, and the associated zoning maps were presented using geographic information system (GIS). Nitrate concentrations in the rural and urban areas were within 0.4-137 mg/L NO 3 − and 2.9-209 mg/L NO 3 − , respectively. Also, 226 (25%) and 104 (24%) of samples in the rural and urban areas, respectively, were detected above the Iran and WHO guideline NO 3 − values of 50 mg/L. The highest levels of NO 3 − , which were found in the western and centra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Nitrate levels ranged between 0.4-137.0 mg L −1 and 2.9-209.0 mg L −1 in rural and urban parts of Iran, respectively. In the two locations, 25% and 24% of water samples' nitrate levels were greater than 50 mg L −1 , with agricultural and residential areas having the greatest values [29]. GNN was related to the N usage efficiency of agriculture and nitrate concentrations in Denmark during the past 70 years [30].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Nitrate levels ranged between 0.4-137.0 mg L −1 and 2.9-209.0 mg L −1 in rural and urban parts of Iran, respectively. In the two locations, 25% and 24% of water samples' nitrate levels were greater than 50 mg L −1 , with agricultural and residential areas having the greatest values [29]. GNN was related to the N usage efficiency of agriculture and nitrate concentrations in Denmark during the past 70 years [30].…”
Section: Introductionmentioning
confidence: 87%
“…It was reported that nitrate concentrations in semi-arid southern India varied from 17 to 120 mg/L, with 54.29% of the groundwater samples exceeding the recommended limit of 50 mg/L [28]. Nitrate concentrations in the rural and urban parts of Iran were 0.4-137.0 mg L −1 and 2.9-209.0 mg L −1 , respectively; the nitrate levels were greater than 50 mg L −1 in 25% of the water samples from agricultural areas and in 24% of the water samples from residential areas [29]. Compared to these two areas, the GNN concentrations in Taiyuan were lower and the pollution status was not serious.…”
Section: Spatial Distribution Characteristicsmentioning
confidence: 94%
“…Infants were found to be at the lowest risk level, which is related to minimal water intake. However, given that infants may be on artificial feeding, which may result in increased water consumption and the possibility that adverse effects for the child may occur even with the nitrate content in water exceeding 10.0 mg/dm 3 , the level of hazard for this category of the population may be significantly higher (Aghapour, 2021). The magnitude of risk for teenagers was approximately 30% lower than that of children, and it remained practically at the same level as that of adults aged 16-18 (Fig.…”
Section: Districtsmentioning
confidence: 99%
“…Numerous Ukrainian studies currently discuss the assessment of drinking water quality from noncentralized water supply sources and its effects on public health (Herasymchuk et al, 2022;Romanchuk et al, 2021;Huschuk et al, 2018;Lototska, Prokopov, 2018, etc.). Foreign scientists from many countries of the world also have investigated this issue, particularly in India (Giri, Singh, 2015;Karunanidhi et al, 2021), Bangladesh (Ghosh et al, 2020), Iran (Parvizishad et al, 2017;Qasemi et al, 2018;Aghapour et al, 2021), China (Yu et al, 2020), Indonesia (Sadler et al, 2016), Pakistan (Khalid et al, 2018), the USA (Wheeler et al, 2015;Rogan et al, 2009), Spain (Zufiaurre et al, 2020), Kenya (Nyambura et al, 2020), Bulgaria (Vladeva et al, 2000), Romania (Moldovan et al, 2020), and others, including the use of geographic information system (GIS) technologies (Ni et al, 2009;Shalyari et al, 2019). However, in our opinion, not enough consideration has been given to the assessment of the health risk to children living in rural residential areas, who are the most susceptible group to the impacts of contaminants that can infiltrate drinking water and food products (Ford et al, 2017), particularly in Zhytomyr region (Valerko et al, 2021).…”
Section: Introductionmentioning
confidence: 99%